Short versions of the Basque MacArthur-Bates Communicative Development Inventories (children aged 8–50 months) - Ezeizabarrena, Maria-José; Garcia Fernandez, Iñaki; Murciano, Aroa (Frontiers in Communication, 2024)
This study provides a brief review of the adaptation of the short MacArthur-Bates Communicative Development Inventories (CDI) instruments into Basque. The study aims to provide the scientific community with several standardized instruments designed to measure the vocabulary size of young children (aged 8–50 months) who are learning Basque, a language spoken in Spain and France. Data from over 2,400 children, obtained using the Basque adaptations of the short CDI parental questionnaires, the BCDI-1s(hort), BCDI-2s, and BCDI-3, revealed the capacity of these instruments to identify the effect of age on the language development of preschool-age children exposed to this language, as has been attested in other (minority and non-minority) languages. The study also examined the effect size of age, sex, and language input. The results showed that sex had a null or very small effect on both lexical development and the rest of the scales, whereas the effect of language input increased as children grew older and was even stronger than the effect of age from 30 months onwards. These findings provide solid ground for discussing the relevance of various factors that affect young children's language acquisition.